HKSI`s all-round support to scholarship athletes
Under the recommendations of National Sports Associations, young people with sports talents may become Scholarship Athletes of the HKSI, where they can receive the highest level of training in the sports they excel, compete with top athletes from around the world, as well as benefit from comprehensive financial, training, education and lifestyle support.